Anti‐Inflammatory Effect of Erythropoietin in the TNBS‐induced Colitis. Issue 2 (23rd November 2016) - Mateus, Vanessa; Rocha, João; Alves, Paula; Mota‐Filipe, Helder; Sepodes, Bruno; Pinto, Rui Manuel Amaro
Abstract: Erythropoietin is a potent stimulator of erythroid progenitor cells, which is able to inhibit NF‐kB activation, due to its pleiotropic properties, thus promoting an anti‐inflammatory effect. As inflammatory bowel disease is a chronic disease with reduced quality of life, and the current pharmacotherapy only induces or maintains the patient in remission, there is a crucial need of new pharmacological approaches. The main objective of this study was to evaluate the effect of erythropoietin in the TNBS‐induced colitis model in mice with a normal intestinal flora. Mice with TNBS‐induced colitis were treated with a daily dose of erythropoietin at 500 IU/kg bw/day and 1000 IU/Kg bw/day IP during 4 days. As to clinical symptoms/signs, erythropoietin attenuated the decreased body‐weight and reduced diarrhoea and oedema of the anus registered in the non‐treated mice group in a dose‐dependent manner. The anti‐inflammatory properties of erythropoietin in the TNBS‐induced colitis were confirmed by suppression of pro‐inflammatory mediators, such as TNF‐α, IL‐1β and MPO, as well as a significant increase in the anti‐inflammatory cytokine, IL‐10, was promoted. These treated mice also presented a reduction in haemoglobin faecal and ALP, suggesting a beneficial effect of erythropoietin in the haemorrhagic focus and destruction of the enterocyte associated with the colon injury induced by TNBS, respectively. The histopathological score was reduced after treatment with erythropoietin, decreasing the severity and extension of the colitis. Furthermore, renal and hepatic biomarkers, as well as haematocrit concentration, remained stabilized after treatment. In conclusion, erythropoietin reduces the inflammatory response associated with TNBS‐induced colitis in mice.